A new species of Ceratostema (Ericaceae) with nearly tubular leaves from the Cordillera del Cóndor, Ecuador - Marco M. Jiménez; Henry X. Garzón-Suárez; Gabriel A. Iturralde (PhytoKeys)
A new species of Ceratostema from the Cordillera del Cóndor in Ecuador is described and illustrated. Ceratostema revoluta is distinguished by its nearly tubular leaves with revolute margins, pulvinate petioles, reddish flowers with white base and brownish to black lobes, short, complanate pedicel with carinate bracteoles appressed to the base and calyx lobes appressed to the corolla and overlapping each other below the middle. The taxonomic similarities of the new species are discussed and information about its distribution, habitat and conservation is provided.